Tolosa-Hunt Syndrome: A Case Report and Review of the Literature (Bangladesh Journal of Neuroscience, 2013)
Tolosa-Hunt Syndrome is a painful ophthalmoplegia which is characterized by periorbital or hemicranial pain, with ipsilateral ocular motor nerve palsies, oculosympathetic paralysis, sensory loss in the distribution of the ophthalmic and occasionally the maxillary division of the trigeminal nerve. Various combinations of these cranial nerve palsies may occur, localising the pathological process to the region of the cavernous sinus/superior orbital fissure. We report the case of a patient presented with severe pain in the right side of face which was periorbital with ipsilateral 3rd,4th, 6th cranial nerve palsies along with ophthalmic and maxillary division of trigeminal nerve involvement. MRI of orbit showed hypo-intense lesion in right cavernous sinus extending to right superior orbital fissure (suggestive of granulomatous infiltration). After taking oral steroid her pain was relieved quickly and cranial nerve palsies reversed within one week. Azathioprin was added and she was completely cured of within next three months.Bangladesh Journal of Neuroscience 2013; Vol. 29 (2) : 130-133